Animal modeling of earthquakes and prediction markets - Adi Schnytzer; Yisrael Schnytzer (Bar-Ilan University, Department of Economics, 2011)
Prediction markets have been shown to generate fairly accurate odds of various events occurring in the future. The forthcoming possibility of natural disasters provides, on occasion, an opportunity for a bet, yet no wide scale and accepted prediction market has arisen despite its obvious importance, probably due in part to its 'politically incorrect' nature, but more importantly to the fact that we have yet to develop accurate forecasting models. Animals, however, have been forced through natural selection to develop elaborate anticipatory mechanisms to predict possible upcoming calamites. Recent studies suggest that animals can, days and sometimes weeks in advance, predict the occurrence of earthquakes. A wealth of recent observations and laboratory studies corroborate this. Natural disasters have lead to the development of 'risk taking' behaviors when the 'odds' of an upcoming disaster outweigh the benefits of maintaining territory, mating, and other basic behaviors. For various historical reasons discussed in this review, this field has had trouble coming of age, with little funding and support from the scientific community, particularly in the US. Due to the great odds at stake and the tremendous economic impact of earthquakes we wish to raise the awareness of this vital topic to the wider scientific community. We present a review of such animal predictive behavior and propose that an early reading of such models might lead to the development of a predictions market by humans.
Keywords: 330; Erdbeben; Prognoseverfahren; Verhalten; Tiere